2017
DOI: 10.1007/s10616-017-0093-4
|View full text |Cite
|
Sign up to set email alerts
|

Persian shallot, Allium hirtifolium Boiss, induced apoptosis in human hepatocellular carcinoma cells

Abstract: This study investigated the potential of Persian shallot extract as an anticancer agent in HepG2 tumor cell line, an in vitro human hepatoma cancer model system. The inhibitory effect of Persian shallot on the growth of HepG2 cells was measured by MTT assay. To explore the underlying mechanism of cell growth inhibition of Persian shallot, the activity of Persian shallot in inducing apoptosis was investigated through the detection of annexin V signal by flow cytometry and expression of some apoptosis related ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In particular, apoptosis, a physiological process of programmed cell death that plays a key role in homeostasis, is suppressed in many cancer cells. Restoring this ability, therefore, is one of the most important strategies for fighting cancer [ 6 – 9 ]. Phytochemicals derived from edible and medicinal plants have been extensively studied for cancer chemoprevention thanks to their demonstrated ability to modulate the enzymes involved in xenobiotic activation/detoxification, to inhibit cell proliferation and/or to induce apoptosis and the differentiation of neoplastic cells [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, apoptosis, a physiological process of programmed cell death that plays a key role in homeostasis, is suppressed in many cancer cells. Restoring this ability, therefore, is one of the most important strategies for fighting cancer [ 6 – 9 ]. Phytochemicals derived from edible and medicinal plants have been extensively studied for cancer chemoprevention thanks to their demonstrated ability to modulate the enzymes involved in xenobiotic activation/detoxification, to inhibit cell proliferation and/or to induce apoptosis and the differentiation of neoplastic cells [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are two main apoptotic pathways: the extrinsic (or death receptor) pathway, and the intrinsic (or mitochondrial) pathway that is regulated by the activation or deactivation of BCL-2 family genes [ 8 , 9 , 24 ]. For this reason, possible molecular mechanisms, such as the intrinsic and extrinsic apoptosis pathways, and apoptotic markers regulating certain tumourigenesis and cell proliferation mechanisms, such as p53, BAX/BCL-2 ratio, cytochrome c, cyclin E2 and cyclin D3 levels, were analysed.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic apoptosis pathway is mostly regulated by Bcl-2 family proteins and the pro-apoptotic protein Bax and the anti-apoptotic protein Bcl-2 are typically involved in apoptosis and cellular proliferation [ 19 ]. Moreover, the ratio of Bax and Bcl-2 has a key role in the development of apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Leelarungrayub et al (2004) indicated that hexane-extract shallot had very high activity on protecting the human erythrocyte from radicals and is possible to be modified for medical plants or commercial product in the future. Sadat Hosseini et al (2017) found that the Persian shallot extract could be considered as a potential candidate for production of drug for the prevention or treatment of human hepatoma. Table 2.…”
Section: Chemical Constituents and Health Benefitsmentioning
confidence: 99%